Effects of the amendment with almond shell, bio-waste and almond shell-based biochar on the quality of saline-alkali soils. (15th September 2022) - Sánchez, Eliana; Zabaleta, Romina; Fabani, María Paula; Rodriguez, Rosa; Mazza, Germán
Abstract: This study aimed to evaluate the effect of the amendment with almond shell bio-waste (AS) and almond shell-based biochar (ASB), in different mass ratios (5, 10, and 15%), on the physicochemical properties of three different saline soils, using the growth of arugula seedlings as a bioindicator of the enhancement achieved. Data were analyzed based on a completely randomized design in a factorial arrangement with four replications. The results showed that the low-salinity soil (T1) presented the best physicochemical characteristics and growth parameters. The addition of AS and ASB in low proportions to the saline soils reduced the pH and electrical conductivity values. An increase in the amendment proportion led to an increase in these variables. Moisture, organic matter, and organic carbon increased, and the cation exchange capacity decreased, generating positive effects on soil quality. The values of exchangeable sodium percentage (ESP) showed that T3 presented the highest sodicity, followed by T2 and T1. The treatment with 5% ASB produced better results regarding total plant length, fresh and dry weights, leaf area, and leaf chlorophyll content. Finally, linear regression models were applied to describe the dependence of the agronomic variables on the ratio of biochar added. Graphical abstract: Image 1 Highlights: Almond shell (AS) and almond shell-based biochar (ASB) were studied for soil amendment. 5, 10, and 15% mass ratios of AS and ASB were added to 3 different saline soils. High ratios of AS and ASB added to soils improved some characteristics of them. The growth of arugula seedlings is a fair indicator of a possible growth enhancement. Arugula seedling yields were enhanced by ASB addition, but not by adding AS.